2002
DOI: 10.2533/000942902777680063
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microstructured Reactor Technology for the Photochemical Chlorination of Alkylaromatics

Abstract: The advantageous application of a falling-film microreactor for a photochemical gas/liquid reaction was demonstrated by the selective photochlorination of toluene-2,4-diisocyanate (TDI). In the microstructured reactor the selectivity to the side-chain chlorinated product 1-chloromethyl-2,4-diisocyanatobenzene (1Cl-TDI) achieved a value of 80% at 55% TDI conversion, whereas the side product toluene-5-chloro2,4-diisocyanate (5Cl-TDI) was formed with only 5% selectivity. The yield of 1Cl-TDI was enhanced by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 10 publications
0
69
0
3
Order By: Relevance
“…A higher selectivity for the formation of monofl uorinated toluene and space-time yields in a falling-fi lm microreactor is reported when compared to the conventional bubble column (Figure 12 ). Ehrich et al [78] used the falling-fi lm microreactor for the photochlorination of toluene-2,4-diisocyanate using both a nickel and an iron reaction plate. They compared the performance of the falling-fi lm reactor performance with the conventional batch reactor ( Figure 13 ).…”
Section: Microreactor Technologymentioning
confidence: 99%
“…A higher selectivity for the formation of monofl uorinated toluene and space-time yields in a falling-fi lm microreactor is reported when compared to the conventional bubble column (Figure 12 ). Ehrich et al [78] used the falling-fi lm microreactor for the photochlorination of toluene-2,4-diisocyanate using both a nickel and an iron reaction plate. They compared the performance of the falling-fi lm reactor performance with the conventional batch reactor ( Figure 13 ).…”
Section: Microreactor Technologymentioning
confidence: 99%
“…[196] Löwe et al entwickelten einen Mikrostrukturreaktor für elektrochemische organische Synthesen (Abbildung 21). [197] Schema [194] Schema 25. Die Reaktion von a-Terpinen mit Singulettsauerstoff ergibt Ascaridol.…”
Section: Mikrostrukturreaktoren Für Gas-flüssigphasen-reaktionenunclassified
“…Wehle et al 83 studied chlorination of acetic acid by chlorine in a MSR at a temperature over 140°C, and the byproduct (dichloroacetic acid) was reduced significantly meaning that there is no need for a costly and time-consuming separation process. Further, Ehrich et al 84 demonstrated photochemical gas-liquid reaction by the selective photochlorination of toluene-2,4-diisocyanate. The space-time yield of 1Cl-TDI, formed by side chain chlorination of TDI, achieved in the MSR significantly exceeded the one of the batch reactor.…”
Section: Gas-liquid Reactionsmentioning
confidence: 99%